Experiences of older adults interacting with a shared autonomous vehicle and recommendations for future implementation. (October 2022) - Booth, Leon; Tan, Tele; Norman, Richard; Anund, Anna; Pettigrew, Simone
Highlights: Older adults interacted with and rode a shared autonomous shuttle bus. Reactions to the autonomous bus were generally positive. Suggestions were made to improve the suitability of the bus for older adults. Physical accessibility was particularly important to the older adults. Demonstrations of AV technology may encourage future uptake among older adults. Abstract: Introduction: A recognised potential benefit of autonomous vehicles is increased mobility for older adults. However, this group is more apprehensive about adoption, which may hinder uptake. Shared autonomous vehicles (SAVs) represent a use case that may be especially relevant for older people due to emerging applications in retirement villages and similar precincts. However, little research has examined the SAV-related concerns of older adults and strategies to address them. This study used an exploratory approach involving SAV exposure to identify strategies that may increase older people's receptiveness to SAVs. Method: Older adults living in retirement villages (n = 63) were interviewed while interacting with an SAV to examine their needs, expectations, and concerns regarding SAVs. The interview data were coded and thematically analysed. Results: Participants recommended the following approaches to ensuring SAVs are useful and acceptable to older adults: providing physical accessibility for those with mobility impairments, comfortable and practical internal layouts, and operating SAVs on convenient routes at useful speeds. Strategies such as exposing older adults to SAVs in operation to encourage uptake and initially ensuring a human assistant is present were suggested methods of increasing receptivity. Discussion: The findings suggest older passengers are likely to share many of the same reactions to SAVs as the broader population, but with a stronger focus on issues relating to accessibility and the physical layout of the vehicles. The solutions to these issues suggested by the study participants may be useful for those designing SAVs for use in older people's settings and beyond.